Pengaruh Tampilan Produk dan Electronic Word of Mouth Terhadap Keputusan Pembelian Pada E-commerce Shopee (Studi Kasus Konsumen Shopee di PT. Gucci Ratu Textile Kota Cimahi) - Ayi Muhiban; Erwinda Karina Putri (Jurnal EMT KITA, 2022)
This research was conducted on Shopee Consumers at PT. Gucci Ratu Textile Cimahi City. The purpose of this study was to determine how big the contribution of the influence of product display and Electronic Word Of Mouth on purchasing decisions either partially or simultaneously at Shopee. The research method that will be used in this research is descriptive method and associative method. In this study, the unit of analysis is the individual, namely the Dyeing-Finishing Department employee at PT. Gucci Ratu Textile Cimahi City who shop online at Shopee. The sample in this study was 129 respondents. Proportional stratified random sampling is the sampling technique used in this study. The method of analysis used multiple linear regression analysis, besides that, the validity and reliability of the research instrument were also tested. Based on the results of the study, it shows that there is an influence either partially or simultaneously on exogenous variables (product appearance and Electronic Word Of Mouth) on endogenous variables (purchase decisions). The implication of this research is that Shopee can review the differences in product display design at Shopee with other online shops to make it more attractive, pay attention to information regarding product prices that must be in accordance with market prices, and increase consumer satisfaction in terms of providing discounts.